Pengaruh Brand Trust, Cita Rasa, Dan Social Media Influencer Terhadap Keputusan Pembelian (International Forum of Researchers and Lecturers, 2025)
Competition in the local culinary business is getting tougher as consumer behavior shifts, placing greater emphasis on product quality and social media recommendations. Nasi Uduk Pemuda, located in Doko Village, Kediri Regency, leverages brand trust, distinctive flavors, and promotions through social media influencers to drive consumer purchasing decisions. This study aims to analyze the influence of brand trust, flavors, and social media influencers on consumer purchasing decisions. The method used in this study is quantitative, with a survey of consumers who have purchased Nasi Uduk Pemuda products. The sample size was calculated using the Slovin formula. Data were analyzed using SPSS 29 through several tests, such as validity, reliability, classical assumptions, multiple linear regression, t-test, f-test, and coefficient of determination (R²). The t-test results indicate that brand trust and flavor have a significant positive influence on consumer purchasing decisions. On the other hand, the influence of social media influencers on purchasing decisions is positive, but not significant. The f-test shows that simultaneously, the three variables significantly influence purchasing decisions, with an R² value of 0.669. This means that 66.9% of the variation in purchasing decisions can be explained by brand trust, taste, and the influence of social media influencers, while the remainder is influenced by other factors not examined in this study. In conclusion, maintaining brand trust, ensuring consistent taste quality, and leveraging promotions through social media influencers remain important strategies in improving consumer purchasing decisions. Nasi Uduk Pemuda needs to continue to maintain and develop these three elements to remain competitive in an increasingly dynamic market.